Lack of response to unaligned chromosomes in mammalian female gametes - Sebestova, Jaroslava; Mac Gillavry Danylevska, Anna; Novakova, Lucia; Kubelka, Michal; Anger, Martin (Cell Cycle, 2012)
Chromosome segregation errors are highly frequent in mammalian female meiosis, and their incidence gradually increases with maternal age. The fate of aneuploid eggs is obviously dependent on the stringency of mechanisms for detecting unattached or repairing incorrectly attached kinetochores. In case of their failure, the newly formed embryo will inherit the impaired set of chromosomes, which will have severe consequences for its further development. Whether spindle assembly checkpoint (SAC) in oocytes is capable of arresting cell cycle progression in response to unaligned kinetochores was discussed for a long time. It is known that abolishing SAC increases frequency of chromosome segregation errors and causes precocious entry into anaphase; SAC, therefore, seems to be essential for normal chromosome segregation in meiosis I. However, it was also reported that for anaphase-promoting complex (APC) activation, which is a prerequisite for entering anaphase; alignment of only a critical mass of kinetochores on equatorial plane is sufficient. This indicates that the function of SAC and of cooperating chromosome attachment correction mechanisms in oocytes is different from somatic cells. To analyze this phenomenon, we used live cell confocal microscopy to monitor chromosome movements, spindle formation, APC activation and polar body extrusion (PBE) simultaneously in individual oocytes at various time points during first meiotic division. Our results, using oocytes from aged animals and interspecific crosses, demonstrate that multiple unaligned kinetochores and severe congression defects are tolerated at the metaphase to anaphase transition, although such cells retain sensitivity to nocodazole. This indicates that checkpoint mechanisms, operating in oocytes at this point, are essential for accurate timing of APC activation in meiosis I, but they are insufficient in detection or correction of unaligned chromosomes, preparing thus conditions for propagation of the aneuploidy to the embryo.
Keywords: Tubulin; Animals; kontrolní body M fáze buněčného cyklu; Mammals; transportní proteiny; Female; proteolýza; komplexy ubikvitinligas; anafáze; aneuploidie; segregace chromozomů; ženské pohlaví; Ubiquitin-Protein Ligase Complexes; párování chromozomů; M Phase Cell Cycle Checkpoints; Oocytes; mikroinjekce; Time-Lapse Imaging; kinetochory; Mice; oocyty; Metaphase; metafáze; myši; Carrier Proteins; Chromosome Pairing; Chromosomes, Mammalian; tubulin; savci; Male; časosběrné zobrazování; Anaphase; histony; Histones; zvířata; mužské pohlaví; konfokální mikroskopie; savčí chromozomy; Aneuploidy; Chromosome Segregation; Mice, Inbred C57BL; Kinetochores; Microinjections; Microscopy, Confocal; myši inbrední C57BL; Proteolysis